2011
DOI: 10.1037/a0023218
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing the time course of lexical and discourse processes through context, coreference, and quantified expressions.

Abstract: How does prior context influence lexical-and discourse-level processing during real-time language comprehension? Experiment 1 examined whether the referential ambiguity introduced by a repeated, anaphoric expression had an immediate or delayed effect on lexical and discourse processing, using an eye-tracking while reading task. Eye-movements indicated facilitated recognition of repeated expressions, suggesting that prior context can rapidly influence lexical processing. However, context effects at the discours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…We found that discourse effects followed lexical ones, both when co-referencing occurred within a clause and when it occurred between clauses. These patterns straightforwardly map onto models of comprehension where lexical processes logically precede discourse processes (Ferreira & Patson, 2007; Huang & Gordon, 2011; Tily et al, 2010), although these accounts would still need to contend with prior evidence of interactivity (Kim & Osterhout, 2005; Kuperberg et al, 2003; Kuperberg et al, 2007; Ledoux et al, 2007; Swaab et al, 2004). While a complete synthesis of these patterns is not yet in hand, we believe that the present research suggests a linguistic architecture that involves both functionally separable levels of representations and interactive mappings along their interfaces.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…We found that discourse effects followed lexical ones, both when co-referencing occurred within a clause and when it occurred between clauses. These patterns straightforwardly map onto models of comprehension where lexical processes logically precede discourse processes (Ferreira & Patson, 2007; Huang & Gordon, 2011; Tily et al, 2010), although these accounts would still need to contend with prior evidence of interactivity (Kim & Osterhout, 2005; Kuperberg et al, 2003; Kuperberg et al, 2007; Ledoux et al, 2007; Swaab et al, 2004). While a complete synthesis of these patterns is not yet in hand, we believe that the present research suggests a linguistic architecture that involves both functionally separable levels of representations and interactive mappings along their interfaces.…”
Section: Discussionmentioning
confidence: 97%
“…Consistent with earlier behavioral and neural studies (Scarborough et al, 1977; Young & Rugg, 1992), we found that these processes are sensitive to the inherent statistics of a target word (frequency of John vs. Earl ), as well as its relational occurrence within a sentence (repetition of John vs. introduction of Eric ). At the discourse level, linguistically specified content is matched with a mental model of the event that integrates across past and current context (Gordon & Hendrick, 1998; Huang & Gordon, 2011). In the case of anaphora, the prominence of the antecedent influences the felicity of the expressions used to co-refer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations